Porous and self-strengthened poly(ε-caprolactone)/calcium sulfate hemihydrate composite fibers for bone regeneration. Issue 17 (1st September 2021) - Zhou, Wen-Yu; Zhou, Yi-Bo; Wang, Shu-Wen; Wang, Peng; Teng, Shu-Hua
Abstract: Porous polycaprolactone (PCL)/calcium sulfate hemihydrate (CSH) composite fibers with different compositions were fabricated via electrospinning by using chloroform/dimethyl sulfoxide (volume ratio = 8:2) as the co-solvent. It was found that the incorporation of fine CSH powders greatly improved the morphology of the PCL fibers and generated continuous, bead-free PCL/CSH composite fibers with the pore diameter varying from 0.2 to 1.1 μm when 20% CSH was added. As compared with the PCL fibers, the PCL/CSH composite fibers also exhibited enhanced thermal stability and hydrophilicity. The tensile strength and elastic modulus of the PCL/CSH fibrous membranes first increased and then decreased with the increase of the CSH content, while their ductility exhibited a sustained decrease. Moreover, after immersion in water, the PCL-20%CSH composite fibers presented a much higher tensile strength than the pristine ones probably due to the self-setting of the CSH powders through the porous structure. In addition, the PCL-20%CSH composite fibers displayed a strong ability to form bone-like apatite after immersion in simulated body fluid for 3 days, which suggests their potential applications in bone tissue regeneration as a novel type of substitute.